Penghindaran Pajak Dari Aspek Keuangan Dan Good Corporate Governance Pada Sektor Perbankan - Indah Tri Purboasih, Nur; Wulandari, Sartika; Meita Oktaviani, Rachmawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2025)
Tax avoidance is an effort made to minimize tax obligations that must be paid by taking advantage of legal loopholes or weaknesses in applicable regulations. This study aims to examine the effect of profitability, leverage, institutional ownership, and independent board of commissioners on tax avoidance. The population in this study were banking sector companies listed on the Indonesia Stock Exchange for the period 2021-2023, the sampling technique used purposive sampling method with certain criteria, obtained a sample totaling 28 companies. This study uses a quantitative approach with secondary data in the form of annual financial report. The data analysis technique used is panel data analysis using Eviews12 software. The results showed that profitability affects tax avoidance. While leverage, institutional ownership, and independent board of commissioner have no effect on tax avoidance.